Integrative and Eclectic Therapy / A Handbook - Dryden Windy (Open University Press, 1992)
An essential sourcebook for practicing and trainee therapists and counsellors. Introduction, The Evolution and Current Status of Psychotherapy Integration, Systemic Integrative Psychotherapy, Cognitive-Analytic Therapy (CAT), Multimodal Therapy, Counselling Skills: An Integrative Framework, Behavioral-Systems Couple Therapy: Selecting Interventions According to Problems Presented, Sex Therapy: An Integrative Model, Family Therapy: Evolving an Integrated Approach, Integrative Encounter, Research on Integrative and Eclectic Therapy, Systemic Integrative Psychotherapy Training, Appendix, Index.